TILSHUNOSLIKDA LINGVOSTATISTIK TAHLIL MUAMMOLARINING O‘RGANILISHI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article provides information about the theoretical and practical work of scientists who have observed the possibilities of linguo-statistical analysis in Uzbek linguistics and the possibilities of linguistic analysis in world linguistics with the help of computer technologies.
Keywords: Computational Linguistics, Linguistics, Modeling, Experimental Phonetics, Areal Linguistics, Corpus Linguistics, Annotated Combinatorial Dictionary, Frequency Dictionary.